2011
DOI: 10.1007/s00606-011-0454-y
|View full text |Cite
|
Sign up to set email alerts
|

Fly pollination of dichogamous Angelica sylvestris (Apiaceae): how (functionally) specialized can a (morphologically) generalized plant be?

Abstract: Because of the flower morphology and high number of insect visitors, plants of the family Apiaceae are regarded as generalists in terms of pollination systems. Recent studies however showed some degree of, at least, ecological specialization in some members of this taxonomical group and indicated interesting patterns of insect visitor behavior: discrimination between umbel sexual phases. To test whether this is true in case of other members of the family, over two years we studied the pollination biology of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 32 publications
(52 reference statements)
2
62
2
Order By: Relevance
“…Vesp Vespidae, LS large Syrphids, SS small Syrphids, LM large Muscoid flies, MM medium Muscoid flies (Faegri and van der Pijl 1966), and, as such, may be easily visited by a wide spectrum of insects, and are thus phenotypically generalized (Ollerton et al 2007). Indeed, our study showed that they are attractive to over 81 species of anthophilous insects, a result comparable to that found in many other members of the family (Knuth 1898; Corbet 1970; Grace and Nelson 1981;Ellis and Ellis-Adam 1993;Zych 2002Zych , 2007Zych et al 2007;Niemirski and Zych 2011). Although the taxonomic spectrum of visitors to our study species extended over 5 systematic orders, most floral visitors to O. palustre flowers belonged to a small number of functional groups within a single order, since 99-100 % visits in 2009-2010 and 85 % visits in 2008 were by Diptera.…”
Section: Pollination Importancesupporting
confidence: 88%
See 4 more Smart Citations
“…Vesp Vespidae, LS large Syrphids, SS small Syrphids, LM large Muscoid flies, MM medium Muscoid flies (Faegri and van der Pijl 1966), and, as such, may be easily visited by a wide spectrum of insects, and are thus phenotypically generalized (Ollerton et al 2007). Indeed, our study showed that they are attractive to over 81 species of anthophilous insects, a result comparable to that found in many other members of the family (Knuth 1898; Corbet 1970; Grace and Nelson 1981;Ellis and Ellis-Adam 1993;Zych 2002Zych , 2007Zych et al 2007;Niemirski and Zych 2011). Although the taxonomic spectrum of visitors to our study species extended over 5 systematic orders, most floral visitors to O. palustre flowers belonged to a small number of functional groups within a single order, since 99-100 % visits in 2009-2010 and 85 % visits in 2008 were by Diptera.…”
Section: Pollination Importancesupporting
confidence: 88%
“…We used a slightly modified version of the observation method of Zych (2007) and Niemirski and Zych (2011). Each full study day would comprise a maximum of six rounds of observations.…”
Section: Ostericum Palustre Bessermentioning
confidence: 99%
See 3 more Smart Citations